1962
DOI: 10.1161/01.cir.25.5.862
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured Papillary Muscle Following Myocardial Infarction with Long Survival

Abstract: Two cases of rupture of a papillary muscle of the left ventricle are presented. We believe that these are the two longest recorded survivals of this complication of acute myocardial infarction. A presumptive clinical diagnosis is possible from the characteristic history of sudden deterioration together with the development of a loud apical systolic murmur. The differential diagnosis and the possibility of corrective surgery in a patient who survives the acute event are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Reported cases of papillary muscle rupture complicating myocardial infarction have been reviewed (Davison, 1948;Craddock and Mahe, 1953;Sanders et al, 1957). The sudden development of pulmonary oedema and the emergence of an apical systolic murmur during the first two weeks after the onset of myocardial infarction were found to be characteristic features in the diagnosis of mitral incompetence due to rupture of a papillary muscle (Sanders et al, 1957;Breneman and Drake, 1962;Adicoff et al, 1963). Unless further myocardial infarction occurs, and apart from the subsequent development of left atrial or ventricular strain, electrocardiography was not reported to show specific changes (Breneman and Drake, 1962;Phillips, De Pasquale, and Burch, 1963).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported cases of papillary muscle rupture complicating myocardial infarction have been reviewed (Davison, 1948;Craddock and Mahe, 1953;Sanders et al, 1957). The sudden development of pulmonary oedema and the emergence of an apical systolic murmur during the first two weeks after the onset of myocardial infarction were found to be characteristic features in the diagnosis of mitral incompetence due to rupture of a papillary muscle (Sanders et al, 1957;Breneman and Drake, 1962;Adicoff et al, 1963). Unless further myocardial infarction occurs, and apart from the subsequent development of left atrial or ventricular strain, electrocardiography was not reported to show specific changes (Breneman and Drake, 1962;Phillips, De Pasquale, and Burch, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…The sudden development of pulmonary oedema and the emergence of an apical systolic murmur during the first two weeks after the onset of myocardial infarction were found to be characteristic features in the diagnosis of mitral incompetence due to rupture of a papillary muscle (Sanders et al, 1957;Breneman and Drake, 1962;Adicoff et al, 1963). Unless further myocardial infarction occurs, and apart from the subsequent development of left atrial or ventricular strain, electrocardiography was not reported to show specific changes (Breneman and Drake, 1962;Phillips, De Pasquale, and Burch, 1963). Chest films might reveal pulmonary vascular congestion with a near normal left atrial size and normal cardiothoracic ratio (DeBusk et al, 1970;Sanders et al, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute ischemic mitral regurgitation (MR) is seen in patients with myocardial infarction (MI), and is associated with increased morbidity and mortality. Severe MR may occur with a frequency ranging from 0.3 to 3 % [ 1 , 2 ] and is more related to the location of the infarction (more commonly seen with inferior MI) rather than the degree of infarction [ 3 7 ]. Left ventricular remodeling, tethering of the mitral valve leaflets, apical displacement of the papillary muscle, and less commonly papillary muscle rupture, contribute to the MR [ 2 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%